Effect of Wearable Sensor-Based Exercise on Musculoskeletal Disorders in Individuals With Neurodegenerative Diseases: A Systematic Review and Meta-Analysis - Li, Xin; Chen, Zhengquan; Yue, Yiming; Zhou, Xuan; Gu, Shuangyu; Tao, Jing; Guo, Haibin; Zhu, Meiwen; Du, Qing (Frontiers in Aging Neuroscience, 2022)
Background: The application of wearable sensor technology in exercise intervention provides a new method for the standardization and accuracy of intervention. Considering that the deterioration of musculoskeletal conditions is of serious concern in patients with neurodegenerative diseases, it is worthwhile to clarify the effect of wearable sensor-based exercise on musculoskeletal disorders in such patients compared with traditional exercise. Methods: Five databases, including PubMed, Cochrane Library, Embase, Web of Science, and Ebsco Cumulative Index to Nursing & Allied Health, were systematically searched. The protocol number of the study is PROSPERO CRD42022319763. Randomized controlled trials (RCTs) that were published up to March 2022 and written in English were included. Balance was the main outcome measure, comprising questionnaires on postural stability and computerized dynamic posturography. Secondary outcome measures are motor symptoms, mobility ability, functional gait abilities, fall-associated self-efficacy and adverse events. Stata version 16.0 was used for statistical analysis, and the weighted mean difference (WMD) was selected as the effect size with a 95% confidence interval (CI). Results: Fifteen RCTs involving 488 participants with mean ages ranging from 58.6 to 81.6 years were included in this review, with 14 of them being pooled in a quantitative meta-analysis. Only five included studies showed a low risk of bias. The Berg balance scale (BBS) was used in 9 studies, and the pooled data showed a significant improvement in the wearable sensor-based exercise group compared to the traditional exercise group after 3-12 weeks intervention (WMD = 1.43; 95% CI, 0.50 to 2.36, P=0.003). A significant change in visual score was found both post-assessment and at 1-month follow-up assessment (WMD = 4.38; 95% CI, 1.69 to 7.07, P=0.001; I2 =0.0%) (Figure 3B). However, no significant differences were found between the two groups in the secondary outcome measures (all p>0.05). No major adverse events were reported. Conclusions: Wearable sensor-based exercise had advantages in improving balance in patients with neurodegenerative diseases, while there was a lack of evidence in motor symptoms, mobility and functional gait ability enhancement. Future studies are recommended to construct a comprehensive rehabilitation treatment system for the improvement of both posture control and quality of life.